2015
DOI: 10.1111/cei.12654
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps can activate alternative complement pathways

Abstract: SummaryThe interaction between neutrophils and activation of alternative complement pathway plays a pivotal role in the pathogenesis of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV). ANCAs activate primed neutrophils to release neutrophil extracellular traps (NETs), which have recently gathered increasing attention in the development of AAV. The relationship between NETs and alternative complement pathway has not been elucidated. The current study aimed to investigate the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
121
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 35 publications
4
121
0
4
Order By: Relevance
“…This is in agreement with recent reports of NETs (48, 49) and suggested that complement is regulated on the NETs to allow opsonization and phagocytosis to terminate the immune response. Clearance of extracellular traps is achieved with the help of DNase I, which cleaves the extracellular DNA and facilitates uptake and clearance of DNA by macrophages (28).…”
Section: Discussionsupporting
confidence: 94%
“…This is in agreement with recent reports of NETs (48, 49) and suggested that complement is regulated on the NETs to allow opsonization and phagocytosis to terminate the immune response. Clearance of extracellular traps is achieved with the help of DNase I, which cleaves the extracellular DNA and facilitates uptake and clearance of DNA by macrophages (28).…”
Section: Discussionsupporting
confidence: 94%
“…For example, a positive feedback mechanism between complement and neutrophil activation has been described in vitro : C5a can activate neutrophils to secrete properdin that, in turn, activates complement on released neutrophil extracellular traps to generate more C5a. This perpetuation of neutrophil-derived inflammation signals might enhance defence mechanisms but also have pathological consequences in diseases such as antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (see below) 38,39 . By contrast, C3a-mediated signalling demonstrated a protective effect in a mouse model of ischaemia–reperfusion injury (IRI), constraining neutrophil mobilization in response to injury 40 .…”
Section: Complement Beyond the Cascadementioning
confidence: 99%
“…NETs can serve as scaffolding that traps platelets [25] and express the pro-thrombotic tissue factor that initiates coagulation [26,27] . We and others have also previously reported that NETs can activate complement [19,28] and this could enhance the Stx-induced complement activation leading to C3b deposition in the glomeruli and on platelets [29,30] , inducing microvascular thrombosis and kidney injury [31] . These adverse procoagulant, pro-inflammatory and complement-activating effects of NETs may be particularly severe in kidneys and fit well the known pathology of STEC-HUS.…”
Section: Discussionmentioning
confidence: 86%